Math, asked by abi0411, 1 year ago

meths geniuses!!! need help!!!!



prove that (x+y)^ 3 + (y+z)^ 3 + (x+y)^ 3 - 3(x+y)(y+z)(z+x) = 2 (x^3 + y^3 +z^3 - 3xy)

Answers

Answered by Anonymous
2
Heya Mate !!!

Here's Your Answer ;-

========================
Step by Step Explanation :-
========================

=> (x+y)^3 + (y+z)^3 + (x+z)^3 - 3(x+y) (y+z) (x+z)

=> (x+y+y+z+x+ z) [(x+y)^2 + (y+z)^2 + (x+z)^2 -(x+y) (y+z)-(y+z)(z+x)-(x+y)(z+x)]

=> 2(x+y+z) (2x^2 + 2y^2 + 2z^2 + 2xy + 2yz + 2xz - x​^2 - y​^2 - z​^2 -3xy -3yz -3xz)

=> 2(x+y+z) (x​^2 + y​^2 + z​^2 - xy - yz - xz)

=> 2(x^3 +y^3 +z^3 - 3xyz)


< Hope It Helps >
Answered by ramanegi1985
0

Answer:

ghost and magic are real I believe on that I have seen ghosts in village

Similar questions